Edukasi Peningkatan Perilaku Hidup Bersih Sehat (PHBS) Dalam Mencegah Penularan Covid-19 Pada Santri (Di Pesantren Persatuan Islam 67 dan Pesantren Ibadurrahman) - Dian Saraswati; Rian Arie Gustaman; Puji Laksmini; Irani Hoeroni (Jurnal Pasca Dharma Pengabdian Masyarakat, 2022)
The Covid-19 pandemic has been a dark time since the beginning of 2020. The virus first appeared in Wuhan, China, made everyone worried. Pengabdian bagi Masyarakat skema Kesehatan (PbM-SK) aims to improve clean and healthy lifestyle in preventing the transmission of COVID-19 among students. The purpose of this activity is to ensure that students in Islamic boarding schools received education about improving PHBS to prevent the transmission of COVID-19. These trainers (students who attended education) will become agents for other students in improving clean and healthy lifestyle to prevent COVID-19. The problem raised from there had been cases of some students who were confirmed positive COVID-19 at Persatuan Islam 67 Islmaic Boearding School and to prevent students from other places obtain COVID-19 such as at the Ibadurrahman Islamic Boarding School